Polymer Membranes for Energy-Efficient Separation and Clean Energy Applications: Materials Design, Performance Trade-Offs, and Future Perspectives - Jibrin Muhammad Yelwa; Auwal Jaji Aliyu (Candela Edutech Indonesia, 2026)
The low energy requirement, modularity, operational flexibility, and tunable transport properties of polymer membranes make them promising technologies for energy-efficient separation and clean energy applications. Compared with conventional thermal separation processes, membrane systems significantly reduce energy consumption and carbon emissions while enabling compact and scalable process integration. Recent advances in polymer chemistry and nanocomposite fabrication have expanded membrane applications in gas separation, desalination, wastewater treatment, solvent recovery, fuel cells, electrolyzers, and electrochemical energy storage systems. This review critically examines the structure–function relationships of membranes in relation to transport phenomena and key performance characteristics, including permeability, selectivity, conductivity, stability, and fouling resistance. Particular attention is given to high-performance materials such as polymers of intrinsic microporosity (PIMs), thermally rearranged polymers, ion-conductive polymers, and mixed-matrix membranes incorporating metal–organic frameworks, covalent organic frameworks, and two-dimensional nanofillers. Recent strategies to overcome the conventional permeability–selectivity trade-off are reviewed together with challenges related to physical aging, plasticization, chemical degradation, and large-scale manufacturability. In addition to material innovation, this review highlights recent developments in advanced fabrication techniques, machine learning-assisted membrane discovery, and sustainable circular manufacturing approaches. Unlike previous reviews focusing on individual applications, this work provides an integrated perspective connecting separation technologies and clean energy systems through common membrane design principles. The development of durable, scalable, and intelligent membrane platforms will be essential for advancing decarbonization, water security, and sustainable industrial production worldwide.